PERANCANGAN GAME ANDROID ENDLESS-RUNNER DENGAN EFEK VISUAL DINAMIS MENGGUNAKAN METODE FOUNTAIN - Dicky Alviriandy (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The rapid growth of the Android-based mobile gaming industry has driven innovation in both visual and gameplay aspects. However, many endless-runner games still present monotonous visuals, making them less engaging for players. This study aims to design and develop an endless-runner game with dynamic visual effects using the Fountain method, which allows the design, implementation, and testing stages to run concurrently, improving development efficiency. The game was developed with Unity using the C# programming language and designed with Figma. Key features include automatic background changes based on score, particle effects during jumps and collisions, and a simple yet functional interface. Black box testing was applied to verify that all features worked as expected. The results showed that menu navigation, character control, collision detection, score calculation, background transitions, and visual effects ran smoothly without errors on Android devices running version 10 or above.This game successfully meets the research objective of producing an endless-runner game that is visually appealing and responsive to player actions.